Student veterans and adjustment to college: Making meaning of military experiences. Issue 5 (4th July 2021) - Sullivan, Nicole; Freer, Benjamin D.; Ulrich, Stefanie
Abstract: Objective: This study examined the relationships among meaning making, military stressor severity, and adjustment to college among student service members/veterans (SSM/Vs). Participants: Participants were 128 SSM/Vs enrolled in postsecondary education from April to June 2016. Methods: Participants completed online self-report rating scales of stressor severity for their most stressful military event, meaning made of that stressor, and adjustment to college. Results: Regression analyses revealed that made meaning of military stressors was associated with more positive academic, social, and emotional adjustment to college. Stressor severity was not associated with adjustment, nor did made meaning moderate the relationship between stressor severity and adjustment to college. Conclusion: These findings provide preliminary evidence that making meaning of stressful military experiences can promote academic, social, and emotional adjustment to college among SSM/Vs and has implications for incorporating meaning making strategies into university and clinical programs aimed at promoting adjustment to college in this population.